Molecular analysis of PIT1, PROP1, LHX3, and HESX1 in patients with combined pituitary hormone deficiency: multicenter study - Bas, Firdevs; Darendeliler, Feyza F.; Oyguner, Oya; Aycan, Zehra; Cetinkaya, Ergun; Berberoglu, Merih; Bundak, Ruveyde (Karger, 2009)
[Abstract Not Available]